Studying the performance of a dehumidifier with adsorbent coated heat exchangers for tropical climate operations. (2nd January 2017) - Oh, Seung Jin; Choon Ng, Kim; Thu, Kyaw; Kum Ja, Marip; Islam, Md Raisul; Chun, Wongee; Chua, Kian Jon Ernest
Abstract : A solid desiccant dehumidifier equipped with adsorbent coated heat exchangers has been developed and investigated experimentally. The main component of the solid desiccant dehumidifier included two heat exchangers that were coated with silica gel regular density (RD) type powder in order to increase water adsorption uptake by improving its heat transfer. A series of experiment were conducted to evaluate two key performance indices, namely, moisture removal capacity and thermal performance, under various operating conditions. Results revealed that the reduction of dehumidification process time by 50% can lead to significant improvement of the mean humidity ratio at outlet up to 9.3 g/kg. The maximum moisture removal was found to decrease from 14.8 to 13.2 g/kg with higher airflow rates arising from the reduced residence time of the process air. It was further observed that the water moisture removal was highly affected by inlet humidity ratio. In addition, marked improvement in thermal performance can be achieved by a lowered hot water regeneration temperature.